Pemilihan Dosen Pembimbing Mahasiswa KKP Menggunakan DIP System - Irma Yunita Ruhiawati; Po Abas Sunarya; Devi Rositawati (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2022)
KKP (Work Practice Course) is a compulsory subject that must be taken by all students of Raharja University (UR) and is one of the prerequisites for taking the Thesis later, accompanied by a supervisor in the completion process. The Advisory Lecturer is one of the biggest determinants of whether or not students pass the KKP course. so the process of choosing a supervisor is a process that determines the life and death of students. It really takes a mature strategy to choose which lecturer is the best, because once one gets a supervisor, the process of completing the KKP will be hampered and harm students who take the course. After the student provides the KKP Research Proposal Form, the Head of Study Program or Sekprodi must enter one by one the fields contained in the form into Microsoft Excel as data collection. In the era of technological development that continues to increase rapidly and as a leading campus based on information technology, it is necessary to have a computerized system, through the DIP (Dashboard iLearning Study Program) method, this system will solve this problem, making it easier for the Head of Study Programs and Secretaries of Study Programs to recap the KKP student data along with supervisors who have been proposed by students through a form in each semester. Keywords—Lecturer; Advisor; KKP; DIP; Form KKP (Kuliah Kerja Praktek) adalah mata kuliah wajib yang harus diambil oleh seluruh mahasiswa Universitas Raharja (UR) dan merupakan salah satu prasyarat untuk pengambilan Skripsi nantinya, didampingi oleh satu dosen pembimbing dalam proses penyelesaiannya. Dosen Pembimbing merupakan salah satu faktor penentu terbesar lulus tidaknya mahasiswa dalam mata kuliah KKP tersebut. sehingga proses memilih dosen pembimbing adalah proses penentu hidup dan mati mahasiswa. Sungguh diperlukan strategi matang untuk memilih mana dosen terbaik, karena sekali salah dapat dosen pembimbing, maka proses penyelesaian KKP akan terhambat dan merugikan mahasiswa yang mengambil mata kuliah tersebut. Setelah mahasiswa memberikan Form Usulan Penelitian KKP, kaprodi atau sekprodi harus menginput satu persatu isian yang ada pada form tersebut ke dalam microsoft excel sebagai pendataannya. Di era perkembangan teknologi yang terus meningkat dengan cepat dan sebagai kampus unggulan yang berbasiskan informatika teknologi maka perlu adanya sistem yang terkomputerisai, melalui metode DIP (Dashboard iLearning Prodi) system ini masalah tersebut akan dipecahkan, sehingga mempermudah kaprodi dan sekprodi dalam merekap data mahasiswa KKP beserta dosen pembimbing yang telah diusulkan oleh mahasiswa melalui Formulir di setiap semester. Kata Kunci—Dosen; Pembimbing; KKP; DIP; Form